Features of Organization of Children with Special Educational Needs Teaching in Secondary Schools - Svitlana Bilous; Lesia Ivanchuk (Pedagogical Discourse, 2014)
The article highlights the organizational and methodological principles to ensure the right for education for children with special educational needs, current problems of their education in comprehensive secondary institutions. The need for a well-considered implementation of relevant teaching methods for special education in comprehensive schools is mentioned in the article. It emphasizes the features of an inclusive, individualized and integrated teaching. The factors of efficient teaching structuring to achieve educational goals are pointed out. The article proves the necessity of positive environment creating, the structure specificity, the methodological content of teaching and raising children with disabilities. There is a special focus on the problems of psycho-pedagogical support of those children in secondary schools, teachers involving in the education of children with special educational needs, their training for correctional process of education. The importance of attracting families to participate in the educational process is mentioned.